The Effects of Soret and Dufour on a Steady MHDFree Convection Flow over an Inclined Porous Plate with Viscous Dissipation (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
This paper deals with the effects of Soretand Dufouron a steady MHD free convection flow over an inclined porous plate with viscous dissipation. The models were non-dimensionalisedand the following parameters arise in the flow: Soret number Sr, Dufour number Du, Prandtl number Pr, magnetic parameter M, Schmidtl number Sc, radiation parameter R, permeability of porous medium K, thermal Grashof number Gr, solutalGrashof number Gm, Eckert number Ec and inclination angle . The influences of these parameters which control the flow were analysedand given a place in this work. The dimensionless governing equations of flow field are solved numerically by collocation weighted residual method. The effects of various parameters on the velocity, temperature and concentration profiles are discussed and displayed graphically